Borrelia hispanica in Ornithodoros erraticus, Portugal - Palma, Mariana (2012)
Clin Microbiol Infect ABSTRACT: Tick-borne relapsing fever (TBRF) is a spirochetal infection caused by the genus Borrelia. The disease is distributed in the Old and New World with many different species reported. In Europe, TBRF is caused by B. hispanica transmitted to man by Ornithodoros erraticus, a soft tick usually found in old premises to shelter pig herds. In Portugal, the first human case of TBRF was reported in 1942 but since the beginning of the 1960s, the disease has rarely been described and seems to either have disappeared or have been undiagnosed. Therefore, in 2009 a survey was undertaken to evaluate the presence of the tick in this type of premises and to evaluate its role as a reservoir of Borrelia. The work was carried out where the ticks were previously reported in the Alentejo and Algarve regions. Of 63 pigpens surveyed, O. erraticus was collected from 19% (n = 12) of these pigpens using CO(2) traps. To evaluate potential Borrelia hosts, both pigs (n = 25) and small rodents (n = 10) inhabiting these pigpens were surveyed for Borrelia presence, by whole blood PCR and/or tissue culture, respectively. All results for pigs and rodents were negative for the presence of B. hispanica. PCR assays targeting the 16S rRNA gene and intergenic spacer region of Borrelia were used. Sequence analysis of the positive samples confirmed the presence of B. hispanica in 2.2% (n = 5) of ticks from a pigpen in Alentejo. These results confirm natural, but albeit low, persistence of this agent in Portugal.